Mediastinal and neck follicular dendritic cell sarcoma treated with definitive radiation therapy using the volumetric modulated arc therapy technique: a case report - Adnan Calcuttawala; Nilesh Deshmane; Jaydeep Pol; Sharad Desai (Precision Radiation Oncology, 2021)
Abstract Follicular dendritic cell sarcoma (FDCS) is a rare malignancy that affects the nodal and extranodal tissues. The mediastinum is a rare site for this tumor, with few published reports and series. Although surgery is the mainstay of treatment for this disease entity, in this report we present a case of mediastinal FDCS treated with definitive radiation therapy (RT) with a near‐total radiological response. A 28‐year‐old woman presented with chest tightness and neck swelling. Radiological findings were suggestive of a conglomerated nodal mass involving the mediastinum and extending superiorly into the anterior neck. Biopsy results led to a diagnosis of FDCS. The tumor was deemed unresectable, and definitive RT was planned as the treatment. The patient was treated with volumetric modulated arc therapy to a total dose of 54 Gy in 30 fractions over 6 weeks. Her symptoms had completely resolved at the first follow‐up visit, 3 months after RT completion, with a near‐total radiological response on a contrast‐enhanced computed tomography scan. Although surgery is the standard of care in FDCS, based on the favorable response of FDCS to RT, as in this case, the role of definitive RT needs to be studied in more patients to determine its efficacy in long‐term tumor control as an alternative to surgery.